The dynamic adjustment of factor inputs and its policy implications for major wheat producing areas in China - Chen, S.; Oxley, Leslie; Xu, Z.; Wang, Y.; Ma, H. (2013)
China's major wheat producing areas play a crucial role in ensuring domestic grain production and food security more generally and it is therefore of significance, both empirically and theoretically, to investigate the current situation and future tendencies of the sector. Based on input- and output-oriented DEA models, overall technical efficiency was estimated for the sector, and both radial and slack adjustments were calculated. The course of the dynamic adjustments was identified and presented for factor inputs over the past decade. The results show that the radial adjustments have exhibited a decreasing trend, while structural, slack adjustments have practically disappeared. The course of the dynamic adjustments suggests that there has been a transformation from labor-intensive to land-intensive and capital-intensive operations which will continue to dominate China's wheat production sector. As a consequence, to optimize factor inputs and reduce radical and slack adjustments, it seems necessary that the major wheat producing areas reduce labor inputs; enhance land-intensive operations; and increase agricultural mechanization. © 2013.